Faktor-Faktor Yang Mempengaruhi Risiko Kredit Sektor Perbankan Di Bursa Efek Indonesia - Rifka Ariyani; Evaliati Amaniyah (Management Department of Economics and Business Of Trunojoyo Madura University, 2021)
Bank fundamental factors affect credit risk management policies, because by knowing the internal conditions of the bank, the credit extension policy will be adjusted, in order to minimize the risk of failure or bad credit that creates losses for the Bank. The purpose of this study is to determine the factors that affect credit risk in the banking sector in Indonesia in 2015-2019. This study uses a quantitative approach and statistical tools like multiple regression analysis in conducting hypothesis testing. The results showed that the factors affecting credit risk in the banking sector on the Indonesia Stock Exchange were capital adequacy (CAR) and management quality (BOPO), while profitability (NIM) and liquidity (LDR) did not affect the credit risk (NPL) of the banking sector on the Indonesia Stock Exchange. The coefficient of determination (R2) in this study was 32.1%, so that about 67.9% of the credit risk was explained by other variables not examined in this study.